2020
DOI: 10.21203/rs.2.20704/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Relationship between Sleep Duration, Body Mass Index, Physical Education Classes, Age and High Blood Pressure in Children and Adolescents: A Cross-sectional Study

Abstract: Background In order to study the high blood pressure of children and adolescents and its influencing factors, it provides evidence-based evidence for the high blood pressure prevention of primary and secondary school students. Methods This study is a cross-sectional survey, which uses stratified cluster sampling method to select students from 7 schools to participate in questionnaire survey and physical examination. The correlation between single factor and high blood pressure was analyzed by chi-square test, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 10 publications
(12 reference statements)
0
1
0
Order By: Relevance
“…11,12 Previously, various studies explored the associations between siesta and hypertension or CVDs and revealed that siesta was associated with decreased risk of hypertension or CVDs and other studies also found that too long siesta was associated with increased risk of hypertension. [12][13][14] Too long siesta may decrease the sleep duration at night and affect the total sleep duration of people, indicating that the percentage of siesta in the total sleep duration may be associated with the risk of hypertension or CVDs. 15 Whether the ratio of siesta duration in the total sleep duration was associated with the occurrence of hypertension or CVDs was still unclear.…”
Section: Introductionmentioning
confidence: 99%
“…11,12 Previously, various studies explored the associations between siesta and hypertension or CVDs and revealed that siesta was associated with decreased risk of hypertension or CVDs and other studies also found that too long siesta was associated with increased risk of hypertension. [12][13][14] Too long siesta may decrease the sleep duration at night and affect the total sleep duration of people, indicating that the percentage of siesta in the total sleep duration may be associated with the risk of hypertension or CVDs. 15 Whether the ratio of siesta duration in the total sleep duration was associated with the occurrence of hypertension or CVDs was still unclear.…”
Section: Introductionmentioning
confidence: 99%